A forum for the discussion of issues in zoological taxonomy - Zhang, Zhi-Qiang (Zootaxa, 2007)
Zootaxa was founded in 2001 to help systematists rapidly document the World’s zoological diversity, which includes many undescribed species now threatened by the rapid habitat loss (Zhang 2006). The journal was initially published as a monographic series—each paper or monograph was separately titled, issued and published. Because of the lower limit of four pages for a book or journal issue, manuscripts less than four pages were not published, including short items such as errata that should normally be published.